Evaluation of Yield and Some Physical Quality Characteristics of Different Oat (Avena sativa L.) Genotypes Under Supplemented Irrigation and Rainfall Conditions - Zeki Mut; Necibe Demirtaş; Özge Doğanay Erbaş Köse (Turkish Journal of Agriculture: Food Science and Technology)
Oat is an important cereal used as human food, animal feed and medicinal plant. This study was conducted to determined yield and some physical quality characteristics of 22 oat genotypes in Turkey in rainfall and supplemented irrigation conditions during 2016-2017 growing season at Yozgat/Yerköy, Turkey. Experiments were carried out in randomized complete block design with three replications. In the trials, plant height, panicle length, grain yield, biological yield, thousand grain weight, hectoliter weight and groat percentage were investigated. İn non-irrigated conditions, plant height, panicle length, grain yield, biological yield, thousand grain weight, hectolitre weight and groat percentage were between 54.2-86.2 cm, 14.1-23.3 cm, 116.9-288.1 kg da-1, 593.1-938.9 kg da-1, 24.1- 38.5 g, 40.4-48.4 kg and 63.5-73.6% whereas in supplemented irrigation conditions, plant height, panicle length, grain yield, biological yield, thousand grain weight, hectolitre weight and groat percentage were 65.0-98.7 cm, 15.3-25.7 cm, 226.1-439.6 kg da-1, 979.2-1381.9 kg da-1, 24.2-39.3 g, 43.5-51.0 kg and 62.5-73.0%, respectively. Supplemented irrigation application increased both grain yield and biological yield approximately 1.5 times compared to application based on rainfall. Genotypes G9, G10, G12, G13, G14, G17, G18, G21 and G22 had the highest grain yield in experiments irrigated with both rainfall and supplemented irrigation.